Global Marketplace for Private Health Insurance : Strength in Numbers - Preker, Alexander S. (Washington, DC: World Bank, 2013)
The development challenges of addressing health problems in low- and middle-income countries are daunting but not insurmountable. There are now known and affordable interventions to deal with many aspects of the HIV/AIDS crisis as well as the continued challenge posed by malaria and other major infectious diseases. Three major development objectives of health insurance in low- and middle income countries are highlighted in this volume: securing sustainable financing for health care providers that serve the health needs of vulnerable populations; providing financial protection against the impoverishing cost of illness; and reducing social exclusion from organized health financing and delivery systems. Private health insurance schemes can address the needs of the poor and other vulnerable populations with appropriate combinations of subsidies, risk pooling, household savings, and user charges. The authors of this book argue in favor of a multipillar approach to health care financing in low- and middle-income countries that combines these instruments in addressing the underlying development objectives described above, while putting a strong emphasis on private voluntary health insurance. In this way, private means can make a significant contribution to public ends.